2021
DOI: 10.1093/geront/gnab126
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Everyday ICT Use: The Discursive Construction of Old Age in German Media

Abstract: Background and Objectives Media discourses have the power to construct and perpetuate positive and negative aging images and influence public and individuals’ attitudes. This study aims to critically examine the media portrayal of older persons’ everyday information and communication technology (EICT) usage during the first and second waves of the coronavirus disease 2019 pandemic. Research Design and Methods A total of 51 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The above results are in line with Köttl et al (2021) that asserts that the consumption of ICTs and mobile technologies in the first and 2 nd phase of Covid-19 are extensive and their effects on German audience are varying. However, the influence of ICTs and related technologies are comprehensive in the areas of education but it greatly influence the social behavior of individuals.…”
Section: Fig7 Gender Of Respondents and Impact On Family Bondsupporting
confidence: 90%
“…The above results are in line with Köttl et al (2021) that asserts that the consumption of ICTs and mobile technologies in the first and 2 nd phase of Covid-19 are extensive and their effects on German audience are varying. However, the influence of ICTs and related technologies are comprehensive in the areas of education but it greatly influence the social behavior of individuals.…”
Section: Fig7 Gender Of Respondents and Impact On Family Bondsupporting
confidence: 90%
“…What is more, there is also a bias against older people, termed as "ageism", i.e., the assumption that older adults tend to be both incapable of learning how to use new media and technological devices and disinterested in learning how to use them [35][36][37]. Popular media have reported that even organizations focused on older adults have been found to use images of technology-limited older people [38].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Indeed, much of the extant research on ageing and aged care discourse tends to focus on verbal discourses at the expense of visual ones (see Lichtenstein, 2021), sometimes for pragmatic reasons (eg, that popular news databases for researchers such as ProQuest and Factiva only provide text and not image results), disciplinary conventions, or the historical and ongoing effects of logocentrism (Lemke, 2002;Bock, 2020). The present study responds to calls by scholars (Köttl, et al, 2021) to analyse other types of media (eg, online media), as well as graphics and pictures. It recognises that 'the type of representation of older people in media is more difficult to examine than the simple amount of representation' (Martin, 2009) and, as such, seeks to go beyond simple frequencies of who is depicted to explore in a more nuanced way how these people are depicted and with what implications.…”
Section: Literature Reviewmentioning
confidence: 77%
“…News media coverage of older people and aged care Past research has shown that the media rarely depict older people (Torben-Nielsen & Russ-Mohl, 2012;Lauzen & Dozier 2005;Robinson et al 2007;Fealy & McNamara, 2009;Thayer & Skufca, 2020) and, when they are represented, they are often shown through the lenses of dependency, frailty, cognitive decline, and loneliness (Köttl, et al, 2021;Fraser, et al, 2016;Thayer & Skufca, 2020). This stereotypical and negative coverage can influence how older people think of themselves, as well as influencing expectations of broader society and accompanying public policies.…”
Section: Literature Reviewmentioning
confidence: 99%